2012
DOI: 10.4070/kcj.2012.42.12.853
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Cryptogenic Stroke Associated with Patent Foramen Ovale Coexisting with Pulmonary Embolisms, Deep Vein Thromboses, and Renal Artery Infarctions

Abstract: A paradoxical embolism is defined as a systemic arterial embolism requiring the passage of a venous thrombus into the arterial circulatory system through a right-to-left shunt, and is commonly related to patent foramen ovale (PFO). However, coexisting pulmonary embolisms, deep vein thromboses (DVT), and multipe systemic arterial embolisms, associated with PFO, are rare. Here, we report a patient who had a cryptogenic ischemic stroke, associated with PFO, which is complicated with a massive pulmonary thromboemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Administering both carries a significant risk of critical organ 2 Case Reports in Pulmonology hemorrhages, such as cerebral hemorrhages. Several case reports in the literature reflect similar predicaments [20,21]. Ultimately, we opted for anticoagulation therapy using only rivaroxaban.…”
Section: Casementioning
confidence: 79%
“…Administering both carries a significant risk of critical organ 2 Case Reports in Pulmonology hemorrhages, such as cerebral hemorrhages. Several case reports in the literature reflect similar predicaments [20,21]. Ultimately, we opted for anticoagulation therapy using only rivaroxaban.…”
Section: Casementioning
confidence: 79%
“…A PubMed search using the keywords (Paradoxical embolism) (renal infarction) and (pulmonary embolism) identified only nine cases [8][9][10][11][12][13][14][15][16]. A summary of these cases is presented in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, it was reported that the patients with PFO even might develop arterial thromboembolism with cryptogenic stroke. 3) 6) …”
Section: Discussionmentioning
confidence: 99%